Properties of Gobi Aggregate and Sulfide-Rich Tailings Cemented Paste Backfill and Its Application in a High-Stress Metal Mine - D. Q. Deng; Y. H. Liang; F. C. Huangfu (Advances in Civil Engineering)
This experiment studied the influence law of the strength of CPB affected by tailings content, Gobi aggregate content, cement content, and slurry concentration. The results show, for the CPB with concentration of 77%, when the addition amount of cement reaches 20%, the addition amounts of tailings and Gobi aggregate change within the ranges of 12∼24% and 56∼68%, respectively. The strength of CPB has been gradually improved when the addition amount of Gobi aggregates decreases and the addition amount of tailings increases. In this case, the slump of CPB changes within the range of 26.5 cm∼26.9 cm while the strength of CPB changes within the range of 4.021∼6.845 MPa. Considering future utilization value of tailings, the addition amount is finally set at 16% in production, and the addition amount of Gobi aggregate is set at 64%; namely, tailings: Gobi aggregate = 20 : 80. When the addition amount of cement is 20% (cement/(tailings + Gobi aggregates) = 1 : 4), the strength of CPB reaches 5.62 MPa which meets the production requirement. When the heading machine is used for tunnelling mine roadway in bottom backfill of VCR stope, no collapse or delamination occurs without support, showing good stability and integrity of backfill. When the adjacent stope ore is mined, the backfill with cement content of 11.1%, 14.3%, 20%, and 25% is exposed. In the process of mining, no collapse or delamination occurs. Therefore, the proportion of various backfill materials applied in production is reasonable, being verified by the experiment and field test.